PENGARUH KUALITAS PRODUK, HARGA DAN PROMOSI TERHADAP KEPUTUSAN PEMBELIAN PADA SYARAH BAKERY - Eva Fatmawati; Adi Sismanto (JURNAL MANAJEMEN MODAL INSANI DAN BISNIS (JMMIB), 2020)
This study aims to determine the effect of product quality on purchasing decisions on Syarah Bakery Bengkulu, to determine the effect of prices on purchasing decisions on Syarah Bakery Bengkulu, to determine the effect of promotion on purchasing decisions on Syarah Bakery Bengkulu. to find out the simultaneous influence of product quality, price, and also the promotion on purchasing decisions at Syarah Bakery Bengkulu. The population of this study is permanent customers of Syarah Bakery Bengkulu as the research population numbering 115 customers, from the calculation using purposive sampling it can be seen that the number of samples used in this study were 115 respondents. The research instrument was tested for validity and reliability by looking at the corrected item total correlation and cronbanch's alpha and all were declared valid and reliable. Data analysis techniques used in this study is quantitative data analysis techniques. The results of this study indicate that the product quality variable (X1) has a positive effect on purchasing decisions (Y), indicated by a positive regression coefficient of 0.216 with a sig value of 0.000 <0.005. Price variable (X2) has a positive effect on purchasing decisions (Y), indicated by a positive regression coefficient of 0.239 with a sig value of 0,000 <0.005. The promotion variable (X3) has a positive effect on purchasing decisions 0.110 (Y), indicated by a positive regression coefficient of 0.717 with a sig value of 0.003 <0.005. The F test results state that product quality, price and promotion have a significant and positive effect simultaneously on the decision purchase, obtained a value of 2.0638 with a value of sig = 0,000 <0.005. The influence of the product quality, price and promotion on purchasing decisions is R2 = 51.5% influenced by other variables in this study and the remaining 48.5%.